DEMOGRAPHIC DEVELOPMENT OF REGIONS OF UZBEKISTAN AND DEMOGEOGRAFIC ZONING - Тожиева, Зулхумор (Human Geography Journal, 2015)
The issue of demogeographic zoning in Uzbekistan were studied, considering the demographic development of the regions in the years of independence. For the population of the country, in recent years, the first, second and third child are the result of needs and desires, a sharp decline of a quantity of the next following children, in most cases, can be reasoned that the customs and traditions are gradually adapting to the new economic relations. For this purpose, we have divided the country into three regions – mountainous, desert and mixed. Scientific analysis of demographic processes in these areas allows to reveal the demographic capacity, a condition associated with an increase or decrease in population.